Investigating the Determinants of Islamic Banks’ Financing Quality: A Regional Approach - Fakhrunnas, Faaza; Anto, M. B. Hendrie (International Journal of Islamic Economics and Finance (IJIEF), 2024)
The quality of Islamic banks’ financing is pivotal to determine the banking performance. When an Islamic bank has good quality of financing activities, the bank can generate more financial return due to less exposure to bad financing. This study aims to investigate the determinants of Islamic banks’ financing quality by considering the regional approach. The study utilized non-performing financing as the proxy of bank’s quality financing. The dependent variables consisted of inflation, financing growth, financing to deposit ratio, and asset. In addition, dummy variables were used to identify the period of the COVID-19 pandemic and the regional effect in Java and other regions outside Java. By adopting panel data analysis, this study observed 33 provinces in Indonesia from January 2004 to October 2021. The findings of the study revealed that the determinant of Islamic banks’ financing quality in consumption scheme was different from equity and investment schemes. Moreover, only Islamic banks’ financing quality in consumption scheme had exposure to inflation risk. Regional influence was present in all sorts of financing schemes at the time the COVID-19 pandemic significantly impacted financing quality in investment and consumption schemes. This study suggests that Islamic banking practitioners and financial authorities should understand the different behavior of each financing scheme in order to maintain Islamic banks’ financing quality.